Additively manufactured circularly polarized open‐ended waveguide antenna array based on a linearly tapered double‐ridge polarizer. Issue 10 (28th June 2022) - Ma, Zi Long; Peng, Shao Cong; Chu, Qing‐Xin
Abstract: This article presents a novel circularly polarized (CP) open‐ended waveguide antenna array based on additive manufacturing technology. It is a one‐dimensional four‐element linear array and has a single piece configuration. Its main body is made of dielectric material and partial surfaces are coated by copper films through electroplating to form necessary metal components. Regarding to each element, it is based on a circular waveguide and employs an inbuilt linearly tapered double‐ridge structure to act as a polarizer. To design such a polarizer, different shaped ridges are analyzed and a design evolution is presented and discussed. Compared to the conventional designs, the proposed element and array can avoid structure partitioning during the processing, and effectively reduce the fabrication difficulty and complexity, meanwhile, attain light weights. To validate the design idea, two prototypes corresponding to the element and the array are fabricated and tested. Experimental results indicate that their axial ratio bandwidth (ARBW) are 22% (8.9–11.1 GHz) and 11.8% (9.6–10.8 GHz), and the gain are 6.6 ± 1.1 and 10.6 ± 0.6 dBic, respectively. The proposed element and array could be potentially applied for satellite and other CP communication systems.